2011
DOI: 10.1177/1534765610395617
|View full text |Cite
|
Sign up to set email alerts
|

Secondary traumatic stress, job satisfaction, and occupational commitment in substance abuse counselors.

Abstract: It has been argued that secondary traumatic stress (STS) may adversely affect the retention of counselors and other helping professionals. However, there has been little research regarding the relationship between STS and occupational commitment. The purpose of this study was to examine the relationship between STS and job satisfaction and turnover intention in a sample of 216 substance abuse counselors. Results found STS to significantly predict both job satisfaction and occupational commitment, although job … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 44 publications
2
69
0
Order By: Relevance
“…Thus, workers with high levels of anxiety may be more vulnerable to STS when working with traumatised clients. Regardless of the nature of the relationship between these variables, research has demonstrated an association between STS and lower job satisfaction and occupational commitment [21]. It is possible that STS and other associated sources of distress may contribute significantly to the high levels of staff turnover seen within the AOD sector [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, workers with high levels of anxiety may be more vulnerable to STS when working with traumatised clients. Regardless of the nature of the relationship between these variables, research has demonstrated an association between STS and lower job satisfaction and occupational commitment [21]. It is possible that STS and other associated sources of distress may contribute significantly to the high levels of staff turnover seen within the AOD sector [28].…”
Section: Discussionmentioning
confidence: 99%
“…social isolation) [20]. Furthermore, associations have been made between STS and lower job satisfaction and occupational commitment [21]. The latter are known to contribute to burnout, job turnover and loss to the AOD workforce.…”
Section: Introductionmentioning
confidence: 99%
“…At the personal level, STS may lead to difficulty in enjoying life (Rainville, 2015), thought distortion (Mealer & Jones, 2013), use of drugs and alcohol (Duffy, Avalos, & Dowling, 2015), interpersonal conflicts (Mealer & Jones, 2013), and higher tendency to change career (Duffy et al, 2015). At the organizational level, STS may lead to poor performance (Rainville, 2015), job burnout, turnover, higher intention to change work area (Mealer & Jones, 2013), lower level of job satisfaction (Bride & Kintzle, 2011), and higher level of absenteeism and episodes of sick leave (Rainville, 2015). The aforementioned consequences of STS on health and well-being of ER nurses is alarming toward nurse's ability to provide quality of care (Gavrilovici, Gavrilescu, & Miron, 2013).…”
Section: Figure 1 Hypothesized Study Frameworkmentioning
confidence: 99%
“…The research has shown that between 15% and 38% of social workers experience moderate to high levels of STS (Bride, 2007;Cornille & Woodard Meyers, 1999). Among substance abuse counselors, Bride et al (2009) found that approximately 19% met the criteria for PTSD as a result of their work with traumatized clients, and STS was found to be related to lower job satisfaction and job commitment (Bride & Kintzle, 2011). Similarly, sexual assault and domestic violence counselors showed evidence of STS, such as anger and fear due to their work (S. Baird & Jenkins, 2003;Johnson & Hunter, 1997;Wasco & Campbell, 2002), and their work stress was more likely to carry over into their personal lives (Johnson & Hunter, 1997).…”
Section: Research On Sts In Therapistsmentioning
confidence: 99%